NEUROPLASTICITY EXERCISE: TRY BRUSHING YOUR TEETH WITH YOUR NON-DOMINANT HAND - Tabasum, Syeda T; Khare, Vikram V; Hiralkar, Pranoti; Agroya, Archana; Agroya, Pooja; Hazari, Prachi (International Journal of Psychosocial Rehabilitation, 2020)
The human brain is an organ that improves through mental stimulation. The brain continuously adapts, grows and rewires itself through the growth of new neurons. When people age, it’s common that they experience memory loss and sometimes their fine motor skills – but unless the mental decline is caused by disease, most age related memory and motor skill ability loss is from lack of brain exercise. If you don’t use your brain, it loses its knowledge. Neuroplasticity is the phenomenon in brain where different stimuli lead to increase or decrease in the number of brain cells and remodelling of synapses. Neuroplasticity research has now established beyond doubt that instead being a static cell mass, our brain is actually a dynamic system of neural network that has the capability of significant growth under favourable circumstances.